High virulence is associated with pathogen spreadability in a songbird–bacterial system - Dana M. Hawley; Courtney A. Thomason; Matt A. Aberle; Richard Brown; James S. Adelman (Royal Society Open Science, 2023)
How directly transmitted pathogens benefit from harming hosts is key to understanding virulence evolution. It is recognized that pathogens benefit from high within-host loads, often associated with virulence. However, high virulence may also directly augment spread of a given amount of pathogen, here termed ‘spreadability’. We used house finches and the conjunctival pathogen Mycoplasma gallisepticum to test whether two components of virulence—the severity of conjunctival inflammation and behavioural morbidity produced—predict pathogen spreadability. We applied ultraviolet powder around the conjunctiva of finches that were inoculated with pathogen treatments of distinct virulence and measured within-flock powder spread, our proxy for ‘spreadability’. When compared to uninfected controls, birds infected with a high-virulence, but not low-virulence, pathogen strain, spread significantly more powder to flockmates. Relative to controls, high-virulence treatment birds both had more severe conjunctival inflammation—which potentially facilitated powder shedding—and longer bouts on feeders, which serve as fomites. However, food peck rates and displacements with flockmates were lowest in high-virulence treatment birds relative to controls, suggesting inflammatory rather than behavioural mechanisms likely drive augmented spreadability at high virulence. Our results suggest that inflammation associated with virulence can facilitate pathogen spread to conspecifics, potentially favouring virulence evolution in this system and others.